Jogging in Your Avatar’s Footsteps: The Effects of Avatar Customization and Control Intuitiveness - Rheu, Minjin MJ; Ratan, Rabindra; Sah, Young June; Cherchiglia, Leticia; Day, Tom (Frontiers in Virtual Reality, 2022)
This study examined the effects of customization and intuitiveness of control on the feeling of identification and embodiment, and the actual running performance of game players after playing a digital runner game developed for this research. A 2 (avatar design: customized vs. not customized) x 2 (avatar controls: intuitive vs not intuitive) within-subjects experiment (N = 44) found that playing the game with a customized avatar increased identification with and embodiment in the avatar. However, using unintuitive controls with a customized avatar diminished the feeling of identification. Customizing an avatar increased identification with and embodiment in the avatar. However, using unintuitive controls with a customized avatar diminished the feeling of identification. Further, participants’ running performance was significantly hindered in the customized avatar and unintuitive controls condition, compared to the other conditions. The expectation that identification and embodiment would mediate the effect of avatar customization and control intuitiveness on physical activity was not supported. Together, these results suggest that avatar customization and control intuitiveness should be prioritized when designers intend to use video games to promote post-game physical activity.